Clarity and quality of explanatory notes in financial statements under IFRS. A study of Gaps Expectation gaps for accounting standards (IAS 2, IAS 16, IAS 37 and IAS 38) - Salas Avila, José (2018)
This situational analysis of the clarity and quality of the explanatory notes in the financial statements under IFRS (Obligatory Disclosure), the authorization of approach to the quality of the information delivered in the explanatory notes for 4 accounting information standards, keys in the financial information in the countries of the region, which are IAS 2; Notes relating to inventories, IAS 16; Notes regarding Plant and Equipment Property, IAS 37; Notes regarding Provisions, and IAS 38; Notes regarding Intangible Assets. Additionally, this paper studies the expectations gap (Expectation Gaps) that exists in the information delivered in the notes of the financial statements for three important interest groups of these financial statements; a) external auditors, b) business managers and c) shareholders. The analysis was carried out in financial statements of 6 countries in the region; Argentina, Chile, Colombia, Peru, Paraguay, and Uruguay, were asked the opinion of professionals from the three groups mentioned above and a response of 230 professional opinions of notes was obtained to the financial statements of companies from the 6 countries mentioned above. The conclusions are clear according to the evidence obtained. As expected, third parties interested in the financial statements and their notes estimate that said explanatory notes do not yet have the clarity or quality that the auditors and administrators maintain.